2016
DOI: 10.1093/cid/ciw135
|View full text |Cite
|
Sign up to set email alerts
|

Human Polyomavirus-6 Infecting Lymph Nodes of a Patient With an Angiolymphoid Hyperplasia With Eosinophilia or Kimura Disease

Abstract: Human polyomavirus 6 (HPyV6) is most often detected at the skin surface of healthy individuals. Here, we demonstrate for the first time that HPyV6 also infects internal tissues. We provide direct evidence of HPyV6 infecting a lymph node of a patient with an angiolymphoid hyperplasia with eosinophilia or Kimura disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 18 publications
0
27
0
Order By: Relevance
“…Some recent works have suggested a role of human polyomavirus‐6 in the pathogenesis of ALHE and Kimura disease . However, a recent thorough investigation of polyomaviruses in CLL concluded that there is no association with any of the many viruses tested and this type of leukemia …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some recent works have suggested a role of human polyomavirus‐6 in the pathogenesis of ALHE and Kimura disease . However, a recent thorough investigation of polyomaviruses in CLL concluded that there is no association with any of the many viruses tested and this type of leukemia …”
Section: Discussionmentioning
confidence: 99%
“…35 Some recent works have suggested a role of human polyomavirus-6 in the pathogenesis of ALHE and Kimura disease. 39 However, a recent thorough investigation of polyomaviruses in CLL FIGURE 6 Case 3 showed a centrally ulcerated lesion with granulation tissue underneath, as well as features of lichen simplex chronicus in the adjacent epidermis (A). In the dermis, there was a vascular proliferation arranged in nodules intermingled with prominent inflammatory infiltrate (B).…”
Section: Discussionmentioning
confidence: 99%
“…Compared to healthy, control, skin samples, viral loads in lesional skin samples are several orders of magnitude higher (w1.44e2.37 Â 10 6 copies/LINE repeat vs. w3.11 Â 10 1 copies/LINE repeat for HPyV6, w2.90 Â 10 3 copies/LINE repeat vs. w1.43 Â 10 1 copies/LINE repeat for HPyV7; 7.28e32.27 Â 10 2 copies/cell vs. 0e0.4 copies/cell for HPyV7) (Nguyen et al, 2017;Ho et al, 2015). HPyV6 has been linked to keratoacanthomas, BRAF inhibitoreassociated epithelial neoplasms, and Kimura disease (Beckervordersandforth et al, 2016;Rascovan et al, 2016;Schrama et al, 2014). However, other research has refuted the link between HPyV6/HPyV7 and other skin diseases, including both neoplastic and inflammatory skin diseases (Bergallo et al, 2018;Fava et al, 2016;Frouin et al, 2014;Haeggblom et al, 2017;Schrama et al, 2012;Scola et al, 2012).…”
Section: Human Polyomaviruses 6 Andmentioning
confidence: 99%
“…HPVy7 has been associated with a pruritic rash in two lung transplant recipients . HPyV6 has been linked to Kimura disease, a chronic inflammatory disorder with subcutaneous nodules that is endemic in East Asia . Phylogenetic analysis performed on the LT gene sequences revealed the presence of two distinct clades.…”
Section: Phylogeny Of Human Polyomavirusesmentioning
confidence: 99%
“…208 HPyV6 has been linked to Kimura disease, a chronic inflammatory disorder with subcutaneous nodules that is endemic in East Asia. 209 the orangutan polyomaviruses. These discordant phylogenetic relationships suggest that MWPyV is probably derived from an ancestral recombination event.…”
mentioning
confidence: 99%